Relay start strategies in elite swimmers - Kibele, A.; Fischer, S. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The few studies in the literature concerning the efficiency in relay starts in swimming have focussed mainly on differences in take-off movement techniques (e.g. Gambrel et al., 1991; McLean et al., 2000). Although, trends could be identified, the results are still somewhat inconclusive. In contrast, no study has examined yet whether a reduction of changeover-time in between wall-contact of the income swimmer and the take-off of the outgoing swimmer is a useful relay start strategy as advocated by various swimming experts (e.g. Maglischo, 2003). Two studies were conducted to evaluate the effects of different feedback sources on relay start performance. METHODS: Study 1: Twenty-six junior elite swimmers were examined during a 4-day learning experiment with three relay-starts on each day. Two experimental groups were randomly assigned to two different feedback categories. While one group received feedback on the maximum in the horizontal take-off force the other group received feedback on the changeovertime. Study 2: Sixteen elite swimmers participated in a one-day learning experiment concerning feedback for two different take-off movement techniques. While one group practised the traditional armswing start the second group learned two perform a single-stepstart. Both groups received feedback on the maximum in horizontal force as well a video presentation on their changeover performance. In both studies the time between wall-contact of the income swimmer on the time at for the first 7,5 m of the outgoing swimmer was used as criteria for the relay start performance. RESULTS: Study 1: Swimmers receiving feedback on their horizontal force clearly showed higher improvements in their relay start performance as compared to swimmers receiving changeovertime feedback (F=4,4; p < 0,05). Individual improvements in the force feedback groups could be as much as 0,5 s. While both groups showed similar improvements in the changeover-time only the force feedback group yielded increases in their horizontal force. Study 2 showed that both groups reduced their changeover-time within one day by up to 50 percent (F = 46,7; p < 0,01). While no significant differences between the two take-off movement techniques were found there was a tendency for the single-stepstart to outperform the armswing start. However, despite considerable improvement in the changeover-time no improvements were found in the relay start performance.